PENGARUH PENDIDIKAN NUTRISI TERHADAP POLA MAKAN PENDERITA DIABETES DI BULAN RAMADHAN - Elvin, Said Devi; Nirwan, Nirwan; Yuswardi, Yuswardi (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The Increased consumption of carbohydrates and glucose during Ramadan is very dangerous for people with type 2 diabetes. This is because during Ramadan there is a change in the frequency of meals and meal times, and thus can affect the health of people with Type 2 diabetes. Evidence shows that the adverse effects of Ramadan fasting on increasing blood sugar in people with Type 2 diabetes can be prevented by training and changing healthy diets. This study aims to determine the effect of a nutrition education program based on the Health Belief Model (HBM) on the perception of patients with Type 2 diabetes about eating patterns during the month of Ramadhan in Banda Aceh city. The design of this research was a quasi experiment with a control group. The populations were patients with Type 2 diabetes living across the responsible area of Ulee Kareng’s Community Health Centre, Banda Aceh City. Data was collected using a Likert Scale to measure the perception of patients with Type 2 diabetes about eating patterns during the month of Ramadan based on the HBM theory. The intervention was a Nutrition Education for case groups using guidebooks and booklets. The results were analyzed using the Wilcoxon Signed Rank Test and the Mann Whitney U Test. The results showed that there is a different perception of vulnerability, seriousness, benefits and barriers on eating patterns during the month of Ramadan in the intervention group between before and after the HBM-Based Nutrition Education Program. Another result indicated that there are no differences in perceptions of vulnerability, seriousness, benefits and barriers on eating patterns during Ramadan in the control group between measurement I and measurement II. This study concludes that the HBM-Based Nutrition Education Program is proven to be effective in increasing the perception of people with Type 2 diabetes about eating patterns during Ramadan.